If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = -15 + -3x Solving -3 = -15 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -3 + 3x = -15 + -3x + 3x Combine like terms: -3x + 3x = 0 -3 + 3x = -15 + 0 -3 + 3x = -15 Add '3' to each side of the equation. -3 + 3 + 3x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = -15 + 3 3x = -15 + 3 Combine like terms: -15 + 3 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 5a-3=a+45 | | M+22=50 | | K+18=36 | | W+39=39 | | K+21=42 | | N+36=36 | | 10x-8+136=180 | | (2d+4)=35 | | K+24=36 | | -6x+21-10=9-10x-8 | | 2x-16+x=2x-12+2 | | X+33=50 | | M+32=40 | | 7x/14x | | M+12=12 | | 1.75x+1.50y=337.50 | | 4/3x=90 | | 29(v-990)=-232 | | x^4=0.207 | | 5x=(250/4) | | 16x-3+9x+11+52=180 | | 870=10(w+40) | | C+20=10 | | 16x-3+9x+11=52 | | 111-3s=63 | | 15(z+406)=240 | | n^2+n-1=5 | | 56=8(c-91) | | 20=-b/.2 | | 8=3(x-1)-(x-7) | | 21-4b=13 | | K+3=11 |